From Immersion to Impulse: The Trust Buiding Journey in Digital Commerce - Latifah Latifah; Ramadania Ramadania; Juniwati Juniwati (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
Despite the rapid expansion of digital commerce in Indonesia’s cosmetics sector, the mechanisms through which immersive digital experiences shape consumer decision-making remain insufficiently understood, particularly with respect to the interaction between trust formation and tactile preferences. Addressing this gap, the present study investigates how multidimensional immersive experiences influence impulse buying behavior through the mediating role of trust, while considering need for touch as a moderating factor. Immersive experience is conceptualized through three dimensions that are increasingly prevalent in digital cosmetic marketing, namely augmented reality virtual try-on, live streaming commerce, and social media marketing activities. Employing a cross-sectional research design, data were collected from 451 Indonesian consumers aged 18 to 40 years who had purchased international cosmetic brands via digital platforms within the previous six months. The proposed hypotheses were tested using Partial Least Squares Structural Equation Modeling. The findings indicate that all three immersive dimensions significantly enhance consumer trust, with social media marketing exerting the strongest influence, followed by live streaming commerce and augmented reality virtual try-on. Trust, in turn, has a positive and significant effect on impulse buying behavior. Importantly, the results reveal that need for touch negatively moderates the relationship between trust and impulse buying, suggesting that consumers with higher tactile preferences tend to engage in greater purchase deliberation despite elevated levels of trust. The structural model demonstrates strong explanatory power for both trust and impulse buying. This study contributes to the literature by operationalizing immersive experience as a multidimensional construct and identifying tactile preference as a critical boundary condition in digital consumption contexts. From a practical perspective, the findings offer strategic insights for international cosmetic brands in tailoring digital marketing approaches that align with consumers’ sensory orientations in emerging markets such as Indonesia.